A new species of Gynochthodes (Rubiaceae), G. honbaensis from Hon Ba Nature Researve, southern Vietnam - Oguri, Emiko; Tagane, Shuichiro; Dang, Van-Son; Yang, Chen-Jui; Toyama, Hironori; Tran, Hop; Murakami, Noriaki; Yahara, Tetsukazu (Phytotaxa, 2019)
A new species, Gynochthodes honbaensis (Rubiaceae), from Hon Ba Nature Researve, Khanh Hoa Province, southern Vietnam, is described, with a key to the species of Gynochthodes in Vietnam. This species is phenotypically most similar to G. macrophylla distributed in Nicobar Islands, Thailand, and Peninsular Malaysia, but differs in having smaller leaves, and much longer and glabrous peduncles.